If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + 5(4y + 2) = 10(y + 1) + 9y Reorder the terms: Y + 5(2 + 4y) = 10(y + 1) + 9y Y + (2 * 5 + 4y * 5) = 10(y + 1) + 9y Y + (10 + 20y) = 10(y + 1) + 9y Reorder the terms: 10 + Y + 20y = 10(y + 1) + 9y Reorder the terms: 10 + Y + 20y = 10(1 + y) + 9y 10 + Y + 20y = (1 * 10 + y * 10) + 9y 10 + Y + 20y = (10 + 10y) + 9y Combine like terms: 10y + 9y = 19y 10 + Y + 20y = 10 + 19y Add '-10' to each side of the equation. 10 + Y + -10 + 20y = 10 + -10 + 19y Reorder the terms: 10 + -10 + Y + 20y = 10 + -10 + 19y Combine like terms: 10 + -10 = 0 0 + Y + 20y = 10 + -10 + 19y Y + 20y = 10 + -10 + 19y Combine like terms: 10 + -10 = 0 Y + 20y = 0 + 19y Y + 20y = 19y Solving Y + 20y = 19y Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-20y' to each side of the equation. Y + 20y + -20y = 19y + -20y Combine like terms: 20y + -20y = 0 Y + 0 = 19y + -20y Y = 19y + -20y Combine like terms: 19y + -20y = -1y Y = -1y Simplifying Y = -1y
| 10r^2-3r-7=0 | | x+24+2x=-2-2x-9 | | 10r^2-57r+35=0 | | x+9=-5x+17 | | -16x-20=-14x+40 | | y^2+2.25=-3y | | 9x^2+42x+49= | | 3n+1=-25 | | 4x-(2x-4)=-2x+12 | | 8p+7-9p= | | 15p^2+20p-160=0 | | 18-5x=9+4x | | 9-18=36x | | 3x+2(2x+1)=-43 | | 4x-(2x-4)=-x+12 | | 7n^2+17n+6=0 | | 3(5k-6)=2(3k+4) | | 4(x+5)=5(x-8) | | 6x-2(x-8)=4(x+1)+9 | | 5b^2-43b-70=0 | | 20x+24+6x=3x-6+12 | | 7x+2-6x=10-22 | | b^2+6b-27=0 | | 1.6(5-x)=1.4(3-x) | | 4x^2+12x-6=0 | | 3x-14-2x=6 | | -4(2x+8)=-36 | | 2+22=x+13 | | 4b^2-28b-120= | | 10+6x=x-15 | | 6(s+1)+s+2=8(s-3)+5 | | 7z-15-z+3=0 |